HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN CHEST PASS PADA PERMAINAN BOLA BASKET SISWA SMAN 15 BOMBANA - Trisno; Wolter Mongsidi; Abdul Saman (Universitas Halu Oleo, 2022)
The purpose of this study was to determine whether there is a relationship between arm muscle strength and the ability to perform chest passes in basketball games for students at SMAN 15 Bombana. The population in this study were all male students who participated in extracurricular activities, amounting to 20 people, and as for the sample in this study amounted to 20 people who were taken by total sampling technique. The instrument used to measure the strength of the arm muscles was a push-up test, while the skill test to do a chest pass was a wall pass test. The research data were analyzed using the product moment statistical technique with a significant level of 0.05. The results of this study indicate that there is a significant relationship between arm muscle strength and the ability to perform chest passes in basketball games for SMAN 15 Bombana students. Where rxy = 0.85> r table (0.05: 20) = 0.444, (High Correlation) and the coefficient of determination r = 0.72 or 72% of arm muscle strength contributes to the chest-pass ability of basketball